Anatomy of the Cruciate Ligaments of the Knee Joint in a Thai Population - Wongtriratanachai, MD, Prasit; Niwattananun, MD, Nopporn; Rojanasathien, MD, Sattaya (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To study the anatomy of the anterior cruciate and posterior cruciate ligaments. Methods: Twenty-two Thai cadaveric knees without previous surgery were used for anatomical study of the ACL and the PCL for size and location. Results: The anterior cruciate ligament had an average length of 33.1 millimeters, and an average width of 10.0 millimeters. The posterior cruciate ligament had an average length of 33.0 millimeters, and an average width of 11.0 millimeters. By using the Wilcoxon rank sum and sign rank tests, no difference was found between gender, sides, and length (P>0.05). We did find that the middle portion of the posterior cruciate ligament was statistically wider than that of the anterior cruciate ligament (P<0.05). The axis of the femoral attachment of the anterior cruciate ligament tilted forward to the vertical axis an average of 26.3 degrees. The average width of the attachment to the femur and the tibia was 16.3 millimeters and 20.0 millimeters, respectively. The attachment of ACL at femur is more posterior and at tibia is more anterior in Thai population. The posterior cruciate ligament was attached to the anterior part of the lateral surface of the medial femoral condyle. The axis of the attachment aligned with the horizontal. The average widths of the femoral and tibial attachment were 19.7 millimeters and 13.9 millimeters, respectively. Conclusion: Clinical application of these findings to aid in the location of the attachment site of a tendon graft in the surgical treatment of chronic knee instability will benefit Thai patients.